EUROCENTRISM FACTOR IN THE STUDY OF TURK'S ETHNOGENESIS - Maharramov, R.I (Хуманитарни Балкански изследвания, 2020)
Issues of ethnogenesis of Turks for a long period remain the subject of acute controversy. The analysis of written sources, scientific works of historians, historical facts revealed the factors that hinder the objective study of the ethnogenesis of the Turkic peoples, and even contribute to the falsification of this process. An attempt was made to prove that the opinions of historians are unfounded and biased. These findings are based on a comparison of data from archaeological materials and historical literature. In the scientific world, issues of ethnicity, stages of ethnogenesis, and the history of Turkic peoples have often been studied biased. This was a consequence of the fact that many historians, orientalists, Turkologists, philologists, linguists approached the above problems from the position of “Eurocentrism”, which divides peoples into “historical” (cultural) and “unhistorical” (uncultured), into “chosen ones” and “ barbarians. " The main factor hindering the study of history, the process of ethnogenesis of the Turkic peoples, and now is "Eurocentrism." Over the centuries, historical science has changed its main purpose and function - study, research, and began to turn into a tool that serves the specific interests of politics. Historians of different times and peoples began to distort and falsify the essence of historical facts, processes and events. It is this circumstance that is the main factor that hinders the objective, scientific solution to the problem of ethnogenesis of the Turks.